The Mechanical Behavior of the Glued-in Plate Connection: An experimental study on bonded timber connections - Vernersson, Linn; Örndal, Vendela (My University, 2025)
Glued-in plates is a novel connection for timber construction and limited research has been done on the subject. The connection consists of a timber element with a slot, in which a steel plate is mounted and set with adhesive. Previous research shows that this connection has many advantages compared to traditional timber fastening methods. Similarities can be found with the glued-in rod connection, where both connections are made with the same three materials and have the same basic mechanical behavior. In this project, an experimental study was conducted where different parameters were investigated to gain further insights in the load carrying capacity of the glued in plates connection. Geometrical parameters were changed depending on the test series, and one of the main focuses was to investigate the properties of the glue dowel formed in the perforation of the steel plate. Results from the experimental testing shows that glue dowels increase the load capacity of the connection and contributes a less brittle failure compared to unper forated plates. The shear area of the glue dowel has a linear increasing correlation to the load capacity. Both plate thickness and embedment length have an influence on load capacity up to a certain limit and then plateaus. Distributing the perforation of the plate, gives a higher load capacity due to a better stress distribution in the adhesive. Although, the perforation should not be placed closer than 2.5 times the dowel diameter to the edge of the plate to ensure that there is no failure in thetimber. The connection is proven to exhibit high stiffness and strength. However, there are many areas that need studying before the connection can be used in real life applications. One of the areas is how the application of adhesive should be con ducted for reliable results and practical use, while also studying the occurrence of air bubbles. Furthermore, a design standard with demands, requirements and calcculation method should be developed as to consider all aspects and variables of the connection design.
Keywords: glued-in plates, timber connection, bonded connection, experimental testing, pull-out testing, glue dowel